Formation, antimicrobial activity, and controlled release from cotton fibers with deposited functional polymers. Issue 8 (30th October 2015) - Kim, Suyeon; Nakamatsu, Javier; Maurtua, Dora; Oliveira, Fernando
ABSTRACT: Chitosan and alginate are biopolymers with interesting bioactivity that can be transferred to cotton fibers for medical and health care applications. These polymers in solution can be attached onto cotton fibers by a layer‐by‐layer technique. Confirmation of polymer deposition onto fibers was verified by morphology analysis, coomassie blue dye coloration, and contact angle of water on fibers. Also, weight gain and level of whiteness after each layer deposition were determined. Antimicrobial activity on treated cotton samples against E. coli and S. aureus was evaluated after each layer deposition and high inhibition rate of bacteria growth was observed in samples with chitosan outer layer (∼ 100%). Polyelectrolyte layers on cotton fibers not only provide interesting bioactivity by themselves, but can also serve as a matrix for small bioactive molecules. In this regard, a model molecule was added during sample preparation to study its release behaviors in a buffer solution by monitoring with UV–vis spectroscopy. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43054. Abstract :